Quantification of the Trömner signs: a sensitive marker for cervical spondylotic myelopathy - Chang, Chein-Wei; Chang, Kai-Yin; Lin, Swei-Ming (European spine journal, 2011)
The Trömner sign is commonly used as a clinical neurological examination for upper motor neuron lesions above the fifth or sixth cervical segments of the spinal cord. This study aims to assess and quantify the Trömner signs utilizing electrophysiological test, and correlate to the severity of cord compression in cervical spondylotic myelopathy (CSM). We enlisted 46 CSM patients, and 30 healthy persons as controls. Manual Trömner and Hoffmann signs were tested in all subjects. By using a self-designed instrument, we performed electrophysiological assessments for the Trömner signs in patients and controls. Parameters of conduction latencies and amplitude of muscle action potentials were measured and compared with the cord compression ratios in CSM patients. The results showed a greater diagnostic sensitivity for the quantified Trömner signs in comparison to those of manual Trömner signs and Hoffmann signs. We found a positive correlation between the amplitude of muscle action potentials obtained in the Trömner signs and the cord compression ratios in the patients with CSM. In conclusion, the Trömner signs can be measured by electrophysiological assessments. We demonstrate a new quantification method for an established neurological sign. Not only is Trömner sign a highly sensitive test in clinical neurological examination, the electrophysiological assessment of this sign can also serve as an objective marker for evaluation of the severity of cervical cord compression.